Dielectric Properties and Breakdown of the Gate Oxide in the MOS Structure - Ladislav Harmatha; Peter Valent; Juraj Racko (Communications - Scientific letters of the University of Zilina, 2010)
The article treats the methodology of measuring the breakdown voltage on Si-based MOS structures. Identification of defects in the thin gate oxide is performed using the Weibull statistical analysis. By comparing the current and capacitance measurements on MOS structures we determined the influence of the defect charge in the oxide upon the parameters characterizing the breakdown. A higher occurrence of defects was correlated with elevated values of the flat band voltages. This verifies the hypothesis of an increased destruction of MOS structures caused by electrically active defects arising in the course of thermic oxidation and pre-oxidation treatment of the surface of silicon.